Description of two new Aulacidae (Hymenoptera: Evanioidea) from Japan - Turrisi, Giuseppe Fabrizio; Konishi, Kazuhiko (Zootaxa, 2011)
Two Aulacidae, Aulacus uchidai Turrisi & Konishi, sp. n. and Pristaulacus superbus Turrisi & Konishi, sp. n., are described and illustrated from females recently collected in Japan. Aulacus uchidai is recognizable among the other Palaearctic Aulacus by the colour pattern, with the metasoma entirely blackish, the weak and not extensive sculpture on upper frons, weakly rugulose-foveolate, the shape of mesosoma with propodeum declivous, the moderately long and slender apical lobe of hind coxa and the ovipositor length, 0.6–0.9× fore wing length. Pristaulacus superbus is a large species (length: 15.3–17.3 mm) with a long ovipositor (1.5× fore wing length), readily distinguishable from other Palaearctic Pristaulacus by the blue to dull green metallic hue on head and mesosoma, the entirely black metasoma and one tooth-like process on each side of hind surface of propodeum. Including the two new species, the number of Japanese Aulacidae is now nine, two species of Aulacus and seven species of Pristaulacus. Images of both species are freely available at the web site: http:/ /morphbank.net. A revised key for the identification of the Japanese Aulacidae is provided.